Effects of Canagliflozin on Fatty Liver Indexes in Patients with Type 2 Diabetes: A Meta-analysis of Randomized Controlled Trials - Boyu Li; Ying Wang; Zhikang Ye; Hui Yang; Xiangli Cui; Zhenjun Wang; Lihong Liu (Frontiers Media S.A., 2018)
PURPOSE: Non-alcoholic fatty liver disease (NAFLD) affects about 75% of patients with type 2 diabetes mellitus (T2DM). We conducted a meta-analysis to determine the effect of canagliflozin on fatty liver indexes in T2DM patients. METHODS: A literature search of PubMed, Embase and Cochrane was conducted up to March 30, 2017. The liver function test and lipid profile were extracted from randomized controlled trials (RCTs) to evaluate the effect of canagliflozin on fatty liver. Weighted mean differences (WMDs) or relative risks and 95% confidence intervals (CIs) were computed by using either fixed or random-effects models. Sensitivity analysis and publication bias were evaluated. RESULTS: Our results showed that canagliflozin decreased serum concentrations of  alanine amino transferase (WMD: -11.68 [95% CI: -18.95, -10.95]; P<0.001), aspartate amino transferase (WMD: -7.50 [95% CI: -10.61, -4.38]; P<0.001), gamma-glutamyl transferase (WMD: -15.17 [95% CI: -17.73, -12.61]; P<0.001), triglycerides (WMD: -0.10 [95% CI: -0.15, -0.05]; P<0.001) but increased low-density lipoprotein cholesterol (WMD: 0.1 [95% CI: 0.06, 0.13]; P<0.001), high-density lipoprotein cholesterol (WMD: 0.06 [95% CI: 0.05, 0.07]; P<0.001) at week 26 or 52. CONCLUSIONS: Our results indicated that canagliflozin may have a protective effect on fatty liver in T2DM patients. The limitation was that the liver biopsy was hard to obtain in published studies. More RCTs specified on NAFLD are needed to get further information.   This article is open to POST-PUBLICATION REVIEW. Registered readers (see "For Readers") may comment by clicking on ABSTRACT on the issue's contents page.